Challenges and Potential Research in Fingerprint Image Recognition - Saparudin Saparudin (Annual Research Seminar (ARS), 2015)
The issues about security of the system and the device are still to be a potential topics in computer technology and networking. The fingerprint image as a kind of human biometric features has been used for over a century and the most widely used for personal recognition in civil, forensic, and commercial areas. In this paper is discussed the latest in trend in fingerprint recognition is viewed from the category of fingerprint images, namely; patent, impressed, and latent. The survey of various research articles indicated that opportunities in the fingerprint identification, particularly the problems in fingerprint image enhancement are topic that potential for researched.